Her majesty’s servants: the tame and the wild under the British Raj - Torri, Davide (Religions of South Asia, 2013)
Through an analysis of colonial and orientalist literature, this article will show how South Asian fauna, through the lenses of Colonial enterprise, came to epitomize a whole system of social relations which can be easily tri-partite: the ruler, the ruled and the unruly. The complex colonial apparatus of dominance and repression clearly surfaces in many of the texts produced by the literates working, living or simply travelling through the British Indian Empire. Fascination for the wildest creatures of the jungle or the domesticated flocks reflected and re-shaped discourses about Western dominance. Eventually it entered European culture and modified our perception of South Asia. As long as the boundaries between the human and the non-human remain thin and blurred, non-human animals were rapidly equated to the human subjects of the Empire. The imperialist discourse, a mythology in the making, was made up of a series of performative utterances used to conveniently describe and to shape the new world. A world to be subjugated, tamed and ruled upon by a self-appointed superior authority. The living landscape of South Asia cannot escape the literary cage of the Empire. Human and nonhuman indigenous animals, or even the hybrid system they form, are discussed like a vast, uncharted and uncanny new territory to conquest with sword and pen alike. The article eventually argues that the colonialism of the mind exerted by the British Empire did not spare non-human animals and such perdurable effects still linger and affect uncritical policies of exploitation.
Gesehen am 14.12.2020